Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran - Ghahari, Hassan; Vázquez, Xavier A.; Kubisz, Daniel (Zootaxa, 2017)
A checklist of Oedemeridae species recorded from Iran is given. A total of 48 species and subspecies are reported, of which two, Nacerdochroa caspia (Faldermann, 1836) and Oedemera (Oedemera) virescens virescens (Linnaeus, 1767), are recorded here for the first time from Iran. A total of 18 species (37,5%) are Iranian endemics. The most common chorotypes are Turanian (16 species; 33%), Turano-European (8 species; 17%), SW-Asiatic chorotype (7 species; 15%), Sindian (6 species; 13%) and Arabo-sindian (4 species, 8%).